Pentingnya Rasa Malu: Makna Kejatuhan Adam dan Hawa dalam Mencegah Skandal Pejabat Publik Kristen Indonesia: Makna Kejatuhan Adam dan Hawa dalam Mencegah Skandal Pejabat Publik Kristen Indonesia - Karwayu, Andreas Maurenis Putra (Jurnal Teologi Pambelum, 2025)
This paper explores the concept of shame awareness as an important component in preventing scandals in Christian leadership in Indonesia. Through a literature review, this paper examines the implications of the fall of Adam and Eve and the resulting shame for the context of contemporary Christianity. The paper argues that cultivating shame awareness among Christian public officials can foster responsibility, obedience, the ability to resist the temptations of power, personal ambition, and awareness of sin, thus leading to the creation of a healthy Christian living environment. By understanding the dynamics of shame and the message of the story of Adam and Eve, Christian public officials in Indonesia will be better prepared to manage the complexities of leadership while upholding moral and ethical responsibilities.